Paralympic Brand and Sponsorship - Knight, Marsha-Gaye (Πανεπιστήμιο Πελοποννήσου, 2019)
The purpose of this study is to gain a deeper understanding of the Paralympic brand in Canada and how the brand is leveraged by its sponsors and to increase the understanding of the Canadian Paralympic Committee (CPC) as it relates to sponsor activation and motivations to partner with the brand. The aim of the study is to contribute to the body of research on the CPC brand and sponsorship and serves as a source of feedback on the brand from a sponsor perspective. With the growth the Paralympic movement globally, and specifically to this case in Canada, it is valuable to understand what the makes the sponsors partner with the CPC and the benefits that they in turn gain from the sponsorship. The specificity of this research is to also focus and highlight best practices of CPC sponsors within the sponsorship landscape in Canada. The research questions that this study seeks to answer are: How is the Paralympic brand perceived in Canada? What are the motivations behind sponsoring the brand? How do sponsors activate around the brand? What are the strengths, weaknesses, opportunities and threats (SWOT) of the Paralympic brand? The first question outlines how the Paralympic brand is viewed in Canada from the perspective of the CPC, their sponsors and Paralympians. The second question seeks to understand the reasons and motivations for the sponsors to partner with the CPC brand and how they measure the success of their objectives. The third question provides insight on the different ways in which the partners activate around the Paralympic brand and how it is leveraged for their corporate objectives. The fourth question seeks to evaluate the CPC brand and sponsorship platform to bring to light the strengths, weaknesses, opportunities and strengths from the mentioned stakeholders.
Keywords: Paralympic Games - Management; Paralympic Games - Marketing; Sports sponsorship; Παραολυμπιακοί αγώνες - Διοίκηση και οργάνωση; Παραολυμπιακοί αγώνες - Μάρκετινγκ; Αθλητική χορηγία; Sponsorship; Paralympic Movement; Paralympic Games